The Effect of Polysaccharide Peptide (PsP) Administration on Lowering Triglyceride Level in Smokers with Dyslipidemia - Titin Andri Wihastuti; Wiesye Roryn Sanyoto; Zahra Nazkiano; Faza Zahruna Fakhra; Kumboyono Kumboyono; Indah Nur Chomsy (Universitas Tribhuwana Tunggadewi, 2026)
Cigarette smoking is a major contributor to health problems worldwide and is highly prevalent in Indonesia, especially among young adult males. Nicotine in cigarettes disrupts lipid metabolism, leading to increased triglyceride levels and dyslipidemia, which are closely related to the double nutrition problem, characterized by abnormalities in the lipid profile. Smoking induces these abnormalities, indicating the need for antioxidant administration. This study aims to investigate the effect of Polysaccharide Peptides from Ganoderma lucidum on lowering triglycerides lipid profile level in active smokers with dyslipidemia. This experimental study used a pretest-posttest control group design involving 28 active smokers aged 18-21 years with dyslipidemia. Subjects were assigned to either a polysaccharide peptide (PsP) therapy group, receiving PsP extracted from Ganoderma lucidum, or a control group. Fasting serum triglyceride concentrations were measured before and after treatment. Statistical analyses used paired and unpaired t-tests to assess triglyceride level changes. The results showed a significant lowering of triglyceride levels in the PsP-treated group (p= 0.006). While the difference before and after PsP administration reached marginal statistical significance (p= 0.059), clinical improvement in triglyceride profiles was observed compared to controls. In conclusion, Ganoderma lucidum-derived PsP lowers triglyceride lipid profiles in smokers with dyslipidemia. These findings support the use of PsP as a therapeutic herbal intervention to improve lipid metabolism disturbed by smoking-induced inflammation.